EWSR1‐CREM fusion in pulmonary mesenchymal neoplasm showing distinctive clear cell morphology. Issue 12 (1st October 2020) - Komatsu, Masato; Sakai, Yasuhiro; Nishikubo, Megumi; Tane, Shinya; Nishio, Wataru; Kajimoto, Kazuyoshi; Hirose, Takanori
Abstract : EWSR1 ‐ CREM gene fusions were recently discovered in several mesenchymal and epithelial tumors, including myxoid mesenchymal tumors of the central nervous system, rare cases of soft tissue clear cell sarcoma and angiomatoid fibrous histiocytoma, and hyalinizing clear cell carcinoma, which implicates the potential phenotypic diversities of tumors harboring an EWSR1 ‐ CREM fusion. We herein present an exceedingly indolent pulmonary mesenchymal tumor showing distinctive clinicopathological features. This tumor histologically displayed a small nest and alveolar pattern consisting of monomorphic clear cells intermingled with dilated anastomosing vasculature. Immunophenotypically, tumor cells were positive for vimentin and focally positive for synaptophysin, but negative for many immunohistochemical panels including keratins, EMA, desmin, mesothelial markers, melanotic markers, smooth muscle actin, inhibin and S‐100 protein. Interestingly, RNA sequencing identified an in‐frame EWSR1 ‐ CREM fusion, which was confirmed by subsequent real‐time/reverse transcription polymerase chain reaction and fluorescence in situ hybridization assay. Clinical follow‐up showed no evidence of recurrence and metastasis. Our pathological findings further expand the phenotypic spectrum of tumors associated with EWSR1 ‐ CREM fusions, implying the emergence of a possible novel tumor entity.